2008
DOI: 10.1111/j.1447-0349.2008.00533.x
|View full text |Cite
|
Sign up to set email alerts
|

Community psychiatric nurses' experience of working with people who engage in deliberate self‐harm

Abstract: This paper reports on a study that explored community psychiatric nurses' experiences of working with people who self-harm. Interpretative Phenomenological Analysis was used with eight experienced community psychiatric nurses who participated in semi-structured interviews. Established quality control procedures were utilized including audit of the analysis process and validating the results with participants. The participants described struggling to conceptualize self-harm behaviour and generally reported find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 49 publications
5
66
0
Order By: Relevance
“…Two main themes were identified: (1) 'being burdened with feelings', which included sub-themes around feeling fearful of the patient's life-threatening actions, feeling frustration and abandonment; and (2) 'balancing professional boundaries', including sub-themes around managing personal feelings, maintaining a professional relationship, and wanting better care for the patient. Similar themes were identified from interviews with community psychiatric nurses in another 42 C. Fox qualitative study, whereby nurses reported working with clients who self-harm as stressful, particularly in relation to their professional responsibility to manage risk, and the emotional effect it had upon themselves (Thompson et al, 2008). Interviews with medical professionals have also highlighted barriers in the development of a relationship with individuals who self-harm, whereby doctors and nurses report believing that patients needed to be listened to in a particular way, and that they do not have the specialist skills needed to do so (Anderson et al, 2003).…”
Section: Introductionmentioning
confidence: 59%
“…Two main themes were identified: (1) 'being burdened with feelings', which included sub-themes around feeling fearful of the patient's life-threatening actions, feeling frustration and abandonment; and (2) 'balancing professional boundaries', including sub-themes around managing personal feelings, maintaining a professional relationship, and wanting better care for the patient. Similar themes were identified from interviews with community psychiatric nurses in another 42 C. Fox qualitative study, whereby nurses reported working with clients who self-harm as stressful, particularly in relation to their professional responsibility to manage risk, and the emotional effect it had upon themselves (Thompson et al, 2008). Interviews with medical professionals have also highlighted barriers in the development of a relationship with individuals who self-harm, whereby doctors and nurses report believing that patients needed to be listened to in a particular way, and that they do not have the specialist skills needed to do so (Anderson et al, 2003).…”
Section: Introductionmentioning
confidence: 59%
“…In addition, a particular challenge seemed to exist early in an admission where the clinician may feel particularly responsible for patient safety, and recovery and management were seen as more suitable once the patient moved beyond an initial acutely-unwell presentation and passive role (see Davidson, O'Connell, Tondora, Styron, & Kangas, 2006;Thompson, Powis, & Carradice, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Risk assessment and management are major components of contemporary mental health practice. Risk, described as "the likelihood of an adverse event happening" (Muir-Cochrane & Wand, 2005, p. 5), can include patient aggression (Daffern & Howells, 2009), suicide and self-harm (Thompson, Powis, & Carradice, 2008), absconding (Muir-Cochrane, Mosel, Gerace, Esterman, & Bowers, 2011), substance abuse (Thomson, 1999), and diverse concerns, such as medical comorbidity, exploitation, social exclusion, victimization, and poverty (Kelly & McKenna, 2004;Muir-Cochrane, 2006). The increasing importance placed on risk assessment and management is reflected in not just policy, but also the daily care of consumers by health care professionals worldwide (de Nesnera, & Folks, 2010;Department of Health, 2007;Langan, 2010;Oordt, Jobes, Fonseca, & Schmidt, 2009).…”
mentioning
confidence: 99%
“…Healthcare professionals who are empathetic and compassionate encourage increased disclosure by patients about concerns, symptoms and behaviour, and are ultimately more effective at delivering care (Larson 2005). Conversely, negative reactions can cause a patient to feel that the clinician is hostile, unsympathetic and uncaring, putting the therapeutic relationship at risk (Thompson 2008). For example, negative reactions among healthcare professionals to self harming behaviour are common (Royal College of Psychiatrists 2010), and typically result from The death of a patient by suicide can severely affect mental health professionals, particu larly if it occurs despite major efforts to intervene.…”
Section: The Importance Of Compassionmentioning
confidence: 99%